Cyclic behavior of semi-rigid precast concrete beam-to-column subassemblages with rapid assembly connections. (1st April 2022) - Xue, Weichen; Hu, Xinyu; Dai, Lingjie; Zhu, Bin
Abstract: In this paper, the semi-rigid precast beam-to-column joint subassemblages based on corbel-shoe connection system with rapid assembly characteristics were proposed and experimentally investigated. Four full-scaled interior and exterior beam-to-column joints were prepared and tested under cyclic loading keeping a fixed axial compression ratio at 0.5. It was demonstrated that the tested beam-to-column specimens failed characterized by flexural failure of beam end instead of the column or joint core. The arch-like load-displacement curves and stable hysteretic behavior were captured. The proposed precast beam-to-column subassemblages could not only provide ease of construction process but perform well under simulated earthquake action. The similar bearing capacity, stiffness degradation rule and energy dissipation capacity between precast and monolithic joints provided evidence in support of this. Also, the ductility of precast interior and exterior subassemblies (3.8 and 3.3) was 15.2% and 23.1% higher than that of the monolithic counterparts (3.2 and 2.6). The degenerated four-linear restoring force model was proposed and verified. Moreover, the structural performance evaluation and semi-rigid characteristics of tested specimens were discussed. Highlights: Semi-rigid precast beam-to-column joints with corbel-shoe system were proposed. Full-scaled cyclic tests were carried out under an axial compression ratio of 0.5. Proposed beam-to-column joints could achieve the emulative design philosophy. A degenerated four-linear restoring force model was proposed and verified. Structural performance evaluation and semi-rigid parameters were discussed.